Effects of a Family Empowerment Program on Breastfeeding Rates and Duration among Primiparous Mothers after Cesarean Delivery - Udomkanthong, Rawiporn; wariloon, Achara; Suwannasri, Sajee (Journal of The Royal Thai Army Nurses, 2026)
This quasi-experimental study compared breastfeeding rates and duration before and after the implementation of a Family Empowerment Program. The sample included 60 primiparous mothers following cesarean delivery who met the inclusion criteria. Participants were randomly assigned to either a comparison group (n = 30), which received routine postpartum nursing care, or an experimental group (n = 30), which received routine care combined with the Family Empowerment Program. The research instruments included: (1) the Family Empowerment Program designed to support breastfeeding, (2) educational materials promoting breastfeeding, and (3) a structured breastfeeding questionnaire. The instruments were validated by three experts, yielding a content validity index (CVI) of 0.98. The questionnaire demonstrated acceptable reliability with a Cronbach’s alpha coefficient of 0.86. Data were analyzed using descriptive statistics and chi-square tests to compare weekly breastfeeding rates and continuity between the two groups. Findings demonstrated that mothers in the experimental group achieved significantly higher breastfeeding rates and longer breastfeeding duration than those in the comparison group at the .05 significance level. These results underscore the effectiveness of the Family Empowerment Program in improving breastfeeding outcomes among primiparous mothers after cesarean delivery and support its integration into routine postpartum nursing care to strengthen the quality of maternal and child health services.